An Autocrine TNFα–Tumor Necrosis Factor Receptor 2 Loop Promotes Epigenetic Effects Inducing Human Treg Stability In Vitro - Urbano, Paulo C. M.; Koenen, Hans J. P. M.; Joosten, Irma; He, Xuehui (Frontiers in Immunology, 2018)
A crucial issue for Treg-based immunotherapy is to maintain a bona fide Treg phenotype as well as suppressive function during and after ex vivo expansion. Several strategies have been applied to harness Treg lineage stability. For instance, CD28 superagonist stimulation in vitro, in the absence of CD3 ligation, is more efficient in promoting Treg proliferation, and prevention of pro-inflammatory cytokine expression, such as IL-17, as compared to CD3/CD28-stimulated Treg. Addition of the mTOR inhibitor rapamycin to Treg cultures enhances FOXP3 expression and Treg stability, but does impair proliferative capacity. A tumor necrosis factor receptor 2 (TNFR2) agonist antibody was recently shown to favor homogenous expansion of Treg in vitro. Combined stimulation with rapamycin and TNFR2 agonist antibody enhanced hypo-methylation of the FOXP3 gene, and thus promoting Treg stability. To further explore the underlying mechanisms of rapamycin and TNFR2 agonist-mediated Treg stability, we here stimulated FACS-sorted human Treg with a CD28 superagonist, in the presence of rapamycin and a TNFR2 agonist. Phenotypic analysis of expanded Treg revealed an autocrine loop of TNFα–TNFR2 underlying the maintenance of Treg stability in vitro. Addition of rapamycin to CD28 superagonist-stimulated Treg led to a high expression of TNFR2, the main TNFR expressed on Treg, and additional stimulation with a TNFR2 agonist enhanced the production of soluble as well as membrane-bound TNFα. Moreover, our data showed that the expression of histone methyltransferase EZH2, a crucial epigenetic modulator for potent Treg suppressor function, was enhanced upon stimulation with CD28 superagonist. Interestingly, rapamycin seemed to downregulate CD28 superagonist-induced EZH2 expression, which could be rescued by the additional addition of TNFR2 agonist antibody. This process appeared TNFα-dependent manner, since depletion of TNFα using Etanercept inhibited EZH2 expression. To summarize, we propose that an autocrine TNFα–TNFR2 loop plays an important role in endorsing Treg stability.